2007
DOI: 10.1051/0004-6361:20066400
|View full text |Cite
|
Sign up to set email alerts
|

MHD simulations of jet acceleration from Keplerian accretion disks

Abstract: Context. Accretion disks and astrophysical jets are used to model many active astrophysical objects, such as young stars, relativistic stars, and active galactic nuclei. However, existing proposals for how these structures may transfer angular momentum and energy from disks to jets through viscous or magnetic torques do not yet provide a full understanding of the physical mechanisms involved. Thus, global stationary solutions have not explained the stability of these structures; and global numerical simulation… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

26
244
4

Year Published

2007
2007
2019
2019

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 207 publications
(274 citation statements)
references
References 49 publications
26
244
4
Order By: Relevance
“…This has been shown with the calculations of magnetized accretion-ejection structures by Ferreira & Pelletier (1995) and confirmed by numerical MHD simulations (Casse & Keppens 2002;Zanni et al 2007). In one sense, making funnel flows involves the same physics as loading mass in magnetized jets.…”
Section: The Disc Truncation Radiussupporting
confidence: 73%
“…This has been shown with the calculations of magnetized accretion-ejection structures by Ferreira & Pelletier (1995) and confirmed by numerical MHD simulations (Casse & Keppens 2002;Zanni et al 2007). In one sense, making funnel flows involves the same physics as loading mass in magnetized jets.…”
Section: The Disc Truncation Radiussupporting
confidence: 73%
“…If the field is slightly below equipartition, rotation remains quasiKeplerian in the disk midplane and angular momentum can be efficiently extracted by magnetic torques to launch a powerful wind from the disk surface, as shown by analytical and numerical 2D solutions of the vertical disk structure (Ferreira 1997;Zanni et al 2007). Pesenti et al (2004) found that a self-similar, steady MHD wind from a warm disk (Casse & Ferreira 2000), with a lever arm parameter λ = (r A /r 0 ) 2 13 could fit the tentative jet rotation signatures observed in the low-velocity [O i] flow (Bacciotti 2002).…”
Section: Extended Mhd Disk Windmentioning
confidence: 99%
“…In case of massive protostellar systems that are formed deeply embedded in molecular clouds, they contribute to the feedback mechanism that can either halt or induce the infall process (Frank et al 2014). Numerical simulations predict the generation of jets from disk winds with the magnetic field playing a prominent role (Zanni et al 2007;Fendt 2006;Ouyed & Pudritz 1997). The regions close to the launch of protostellar jets have been examined using high resolution spectroscopy in optical wavebands leading to a better understanding ⋆ E-mail: sarita@iist.ac.in of the collimation properties and velocity structure at the base (Coffey, Bacciotti & Podio 2008).…”
Section: Introductionmentioning
confidence: 99%